2016
DOI: 10.1002/acp.3260
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Predictors of Superior Face Recognition Ability in Police Super‐recognisers

Abstract: Summary: There are large individual differences in the ability to recognise faces. Super-recognisers are exceptionally good at face memory tasks. In London, a small specialist pool of police officers (also labelled 'super-recognisers' by the Metropolitan Police Service) annually makes 1000's of suspect identifications from closed-circuit television footage. Some suspects are disguised, have not been encountered recently or are depicted in poor quality images. Across tests measuring familiar face recognition, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
135
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(154 citation statements)
references
References 57 publications
12
135
3
Order By: Relevance
“…Davis and colleagues suggested that prosopagnosia could be either developmental or acquired as a consequence of specific cortical neuronal damage (3,4). Overall, exploitation of super-recognizers is invaluable, particularly in lawenforcement and intelligence agencies (5)(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Davis and colleagues suggested that prosopagnosia could be either developmental or acquired as a consequence of specific cortical neuronal damage (3,4). Overall, exploitation of super-recognizers is invaluable, particularly in lawenforcement and intelligence agencies (5)(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…Specific tests have been used to examine facial recognition abilities. These tests include the modified cambridge face memory test and cambridge face perception test (3,10). The correlation between handedness and complex visual analytic skills has been studied before.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At one end of the ability spectrum are Developmental Prosopagnosics (DPs) who may be adversely affected by a neurodevelopmental impairment in processing facial stimuli but display no apparent neurological damage [6,7]. The antitheses are Super-Recognisers (SRs), who compared with the typical population, score higher on tests assessing face perception, simultaneous face matching, and familiar and unfamiliar face recognition [e.g., 1,4,5,8], while performing at about the same level as controls at object recognition [3,4], which suggests that SR, like DP is primarily face-specific.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5]. At one end of the ability spectrum are Developmental Prosopagnosics (DPs) who may be adversely affected by a neurodevelopmental impairment in processing facial stimuli but display no apparent neurological damage [6,7].…”
Section: Introductionmentioning
confidence: 99%